Direct truncation method for order reduction of discrete interval system - Choudhary A.K.; Nagar S.K. (My University, 2025)
This paper presents a direct truncation methodology for reducing the order of large scale interval systems. The algorithm is computationally simple, and intuitively appealing. Numerical examples illustrating the effectiveness of the proposed method are included. © 2013 IEEE.